Administering the Value-Added Tax on Imported Digital Services and Low-Value Imported Goods - Brondolo, John. (Washington, D.C. : International Monetary Fund, 2021)
This technical note and manual (TNM) addresses the following questions: (1) What are the main challenges in administering the value-added tax on imported digital services and the measures that countries have introduced to address the challenges?; (2) What are the main challenges in administering the value-added tax on low-value imported goods and the measures that countries have introduced to address the challenges? ;and (3) What are the key tasks in implementing the measures for improving the administration of the value-added tax on imported digital services and low-value imported goods?
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Business Taxes and Subsidies; National Government Expenditures and Related Policies; Tax Evasion and Avoidance